2018
DOI: 10.3346/jkms.2018.33.e335
|View full text |Cite
|
Sign up to set email alerts
|

Prognosis of Spontaneous Bacterial Peritonitis in Hepatocellular Carcinoma Patients

Abstract: BackgroundSpontaneous bacterial peritonitis (SBP) is a serious infectious complication in patients with liver cirrhosis. However, information about prognosis of SBP in hepatocellular carcinoma (HCC) patients is limited. We investigated the clinical course of SBP in HCC patients.MethodsThis study enrolled patients diagnosed with SBP between 2005 and 2017. Medical records of patients were reviewed and clinical course was compared between the non-HCC and HCC groups.ResultsIn total, 123 SBP cases including 49 HCC … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…inter-group of omental malignant disease and any intergroup of omental benign disease is not statistically significant, and the area under ROC curve is mostly about 0.6. When liver cirrhosis patients with portal hypertension combined with hepatocellular carcinoma (HCC), peritoneum lesions may be spontaneous bacterial peritonitis (SBP)or the source of HCC metastasis [20][21][22]. In SBP patients, the omental echo was usually hyperechoic or highlow mixed echo, with loose structure, no nodule, and the ascites echo was mostly homogeneous, which may be accompanied by the display of parietal peritoneum or mesenteric lymph nodes, so the OS was low.…”
Section: Discussionmentioning
confidence: 99%
“…inter-group of omental malignant disease and any intergroup of omental benign disease is not statistically significant, and the area under ROC curve is mostly about 0.6. When liver cirrhosis patients with portal hypertension combined with hepatocellular carcinoma (HCC), peritoneum lesions may be spontaneous bacterial peritonitis (SBP)or the source of HCC metastasis [20][21][22]. In SBP patients, the omental echo was usually hyperechoic or highlow mixed echo, with loose structure, no nodule, and the ascites echo was mostly homogeneous, which may be accompanied by the display of parietal peritoneum or mesenteric lymph nodes, so the OS was low.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover Tu et al established a multivariate diagnostic model for asymptomatic SBP in cirrhotic patients with ascites based on the blood neutrophil percentage, HCC, MELD, PMN, and renal dysfunction 13 . However, Kim JH et al, in a retrospective study including 123 patients comparing prognosis of SBP between the HCC and non-HCC groups, exceptionally demonstrated that the prognosis of the HCC group was relatively less severe than that of the non-HCC group because of the lower antibiotic resistance rate in the HCC group 10 . We tried to determine the different clinical factors between the two groups; SBP patients with HCC showed higher rates of non-alcohol etiology (74.8% vs. 58.0%) and previous use of antibiotics within 60 days (44.9% vs. 18.8%) than those without HCC.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the prevalence of HCC in cirrhotic patients with SBP is known to be high at approximately 20% 9 . There are a few studies that have evaluated the prognosis in patients with SBP accompanied by HCC [10][11][12][13][14] . However, data evaluating the impact of HCC on initial treatment outcomes and short-term mortality in patients with cirrhosis with complicated SBP are still limited.In this study, we aimed to compare the clinical features including initial treatment responses and short-term mortality of SBP among cirrhotic patients with HCC versus those without HCC.…”
mentioning
confidence: 99%
“…There are a few studies that have evaluated the prognosis in patients with SBP accompanied by HCC [10][11][12][13][14] . However, data evaluating the impact of HCC on initial treatment outcomes and short-term mortality in patients with cirrhosis with complicated SBP are still limited.…”
Section: Introductionmentioning
confidence: 99%